Low-frequency ultrasound irradiation increases paclitaxel-induced sarcoma cells apoptosis and facilitates the transmembrane delivery of drugs - Yang, Tana; Zhang, Yixuan; Wang, Tan; Li, Mo; Zhang, Ying; Zhao, Dan; Xu, Libin; Wang, Xiaobing (Frontiers in Pharmacology, 2022)
Sarcoma is a malignant tumor derived from interstitial tissues and requires comprehensive treatment including chemotherapy. Paclitaxel (PTX) is an active agent against sarcoma, but its effect is not sufficiently acceptable and needs to be improved. Low-frequency ultrasound (LFU) has been documented to improve the efficacy of drugs by inducing reversible changes in membrane permeability; however, the effects of the combined use of LFU and PTX for sarcoma tumors remain unclear and warrant further investigation. We investigated the effects of 30 kHz LFU treatment combined with PTX on sarcoma cells A-204 and HT-1080 by analyzing in vitro apoptosis and cell growth inhibition rates, and determined their antitumor effects by examining tumor weights with or without LFU in the S180 sarcoma xenograft model. Drug concentrations in the subcutaneous tumors were measured using high performance liquid chromatography (HPLC). LFU combined with PTX significantly induced cell apoptosis, and blocked the cell cycle of sarcoma cells in G2/M phase, and furthermore, inhibited the activation of JAK2/STAT3 signaling pathway. Meanwhile, LFU combined with PTX inhibited the expression of PD-L1 in vitro, suggesting the potential of enhanced antitumor immunity by this treatment. LFU combined with PTX significantly inhibited the growth of S180 tumors transplanted subcutaneously in Institute of Cancer Research (ICR) mice, and its enhanced effect may be associated with increased local concentrations of PTX in tumor tissues in vivo, with no significant adverse subsequences on body weight observed. We conclude that the combination of LFU and PTX has synergistic antitumor effects and is a candidate for subcutaneous treatment of sarcoma by further increasing the intracellular concentration of PTX.